The infectious propagules of Aspergillus fumigatus are coated with antimicrobial peptides. (5th January 2021) - Dümig, Michaela; Binder, Jasmin; Gaculenko, Anastasia; Daul, Franziska; Winandy, Lex; Hasenberg, Mike; Gunzer, Matthias; Fischer, Reinhard; Künzler, Markus; Krappmann, Sven
Abstract: Fungal spores are unique cells that mediate dispersal and survival in the environment. For pathogenic fungi encountering a susceptible host, these specialised structures may serve as infectious particles. The main causative agent of the opportunistic disease aspergillosis, Aspergillus fumigatus, produces asexual spores, the conidia, that become dissipated by air flows or water currents but also serve as propagules to infect a susceptible host. We demonstrate that the defX gene of this mould encodes putative antimicrobial peptides resembling cysteine‐stabilised (CS)αβ defensins that are expressed in a specific spatial and temporal manner in the course of asexual spore formation. Localisation studies on strains expressing a fluorescent proxy or tagged defX alleles expose that these antimicrobial peptides are secreted to coat the conidial surface. Deletion mutants reveal that the spore‐associated defX gene products delay the growth of Gram‐positive Staphylococcus aureus and demonstrate that the defX gene and presumably its encoded spore‐associated defensins confer a growth advantage to the fungal opponent over bacterial competitors. These findings have implications with respect to the ecological niche of A. fumigatus that serves as a 'virulence school' for this human pathogenic mould; further relevance is given for the infectious process resulting in aspergillosis, considering competition with the host microbiome or co‐infecting microorganisms to break colonisation resistance at host surfaces. Abstract : The asexual spores (conidia, c ) of the opportunistic fungal pathogen Aspergillus fumigatus are formed on specialized structures (conidiophores, cp ) and serve as infectious particles to cause aspergillosis. This study demonstrates that the defX gene is transcribed in the course of asexual sporulation and that its gene products, AfusinN and AfusinC, are secreted onto the conidial surface. There, these CSαβ defensin‐like peptides exert antimicrobial activity to confer an advantage upon confrontation with competing bacteria.